The Politics of Austerity and the Affective Economy of Hostility: Racialised Gendered Violence and Crises of Belonging in Greece. Issue 1 (February 2015) - Carastathis, Anna
In this article I examine the friction between xenophobic discourses on migration and the crisis caused by the politics of austerity in Greece. On the one hand, an 'excessive' influx of migration is managed through violent means by the state and the para-state; on the other, a 'scarcity' of domestic resources is blamed for a 'rise' in racist attitudes, and the political ascent of a fascist movement-cum-parliamentary party, Xρνσή Aνγή (Golden Dawn). 'Crisis' is said to give rise to 'austerity'—and hostility. Inverting the inverted causal relationship between crisis, austerity and hostility, I problematise representations of hostility towards migrants that construct racism as a consequence of economic conditions or even as the antidote to the 'bitter pill' Greeks have been forced to swallow. I examine how racialised and gendered violence secures the politics of austerity in Greece focusing on three eruptions of violence (the feminicidal acid attack on Konstantina Kouneva, the murder of Shehzad Luqman and the drowning of eleven refugees near the island of Farmakonisi). I draw concrete connections between the politics of austerity and what, drawing on Sara Ahmed, might be termed an 'affective economy of hostility' that articulates racialised and gendered modes of belonging and estrangement. Some bodies are rendered vulnerable and precarious, while others assert an entitled relation to national space while being economically disentitled by austerity measures.